Effect of coconut fiber and egg albumen in concrete for greener environment - Tan, Eng Siang (2010)
This paper is to study the effect of the coconut fiber and egg albumen to the properties of the concrete such as the compressive strength, flexural strength and the drying shrinkage. In this study, a total of 54 cubes (150mm x 150mm x 150 mm) and 54 prisms (100mm x 100mm x 500 mm) were prepared according to three types of mixture and all these samples were cured under two curing conditions which were air and water curing for 7 days, 14 days and 28 days. The three types of concretemixture were concrete containing 0.1% coconut fiber and 1% egg albumen (mix A), concrete containing 0.5% coconut fiber and 5% egg albumen (mix B) and concrete control sample. From the data analyses showed that both the additives of coconut fiber and egg albumen with concrete in different percentage show improvement in the development of the strength. In water and air curing condition, it shows that thesamples in the water curing possess higher strength compare to the air curing samples. But, the strength achieved by the additive in the concrete was still lower than the control concrete. By comparing concrete containing 0.1% coconut fiber and 1% egg albumen with concrete containing 0.5% coconut fiber and 5% egg albumen, the strength of the lower percentage additive was higher than the higher percentage of additive. This can be conclude that, 0.5% coconut fiber and 5% egg albumen was not too capable to be used but there may be some condition that suit or need for such percentage.